(untitled) (Mustansiria Dental Journal, 2018)
Medical status of 679 subjects, who attended a dental department in one of the public clinics in Baghdad, was examined, significant medical histories were found in 133 (19.5%) of the subjects. They included diabetes mellitus (5.31%), hypertension (3.54%), and peptic ulcer (2.21%), adverse drug reactions (1.18%), neurological disease and (0.88%), and blood disorders (0.20%).